Seizure relapse based upon withdrawal period of antiepileptic drugs in pediatric epilepsy patients - Rajat Rana; Soumadip Das; S Ramesh; S Chidambaramnathan; Aravinda Swami; Ajit Singh (Archives of Global Professionals, 2014)
Aim: This study was carried out to quantify risk of seizure recurrence after discontinuation of antiepileptic drugs (AEDs) after varying duration of seizure remission in children with epilepsy and to assess the variables modifying the risk of seizure recurrence. Materials and Methods: Randomized controlled trials that evaluate withdrawal of AEDs after varying periods of seizure remission in pediatric epilepsy patients, which could be unblinded, single-blind, or double-blind. The database searching included Cochrane Epilepsy Group Specialized Register, MEDLINE, EMBASE, CINAHL, WHO Clinical trial register, and the Cochrane Central Register of Controlled Trials. Two independent authors extracted the data and assessed trials for quality. Results: The pooled relative risk ratio (RR) for early AEDs withdrawal and late AEDs withdrawal was assessed as 1.22 (95% confidence intervals [CI]: 0.94-1.57), for type of epilepsy pooled relative risk was 1.52 (95% CI: 0.96-2.41), electroencephalogram (EEG) relative risk was assessed as 1.65 (95% CI: 1.08-2.51) and the underlying etiology relative RR was assessed as 1.65 (95% CI: 1.08-2.51). Conclusion: The high-grade evidence of this study supports that discontinuing AED medication prior to at least 2 seizure free years is associated with higher seizure recurrence risk than waiting for two or more seizure free years in children.